Standard and Advanced Imaging of Hip Osteoarthritis. What the Radiologist Should Know - Huang, Brady K.; Tan, Weiken; Scherer, Kurt F.; Rennie, Winston; Chung, Christine B.; Bancroft, Laura W. (Seminars in Musculoskeletal Radiology, 2019)
Osteoarthritis (OA) of the hip is caused by degeneration of articular cartilage and the underlying bone and can be divided into two types: primary (associated with advancing age) and secondary (subsequent to fractures, avascular necrosis, infection, developmental dysplasia, and femoroacetabular impingement). Radiography remains the first-line imaging modality for diagnosing and monitoring OA, due to its accessibility, low cost, and ease of interpretation. Kellgren-Lawrence and Tönnis classification systems are radiographic OA grading systems used primarily in research, and they reflect the degree of joint space narrowing, sclerosis, cysts, deformity of the femoral head and acetabulum, and osteophytes. Unenhanced computed tomography (CT) provides detailed visualization of the hip joint segments that may be difficult to appreciate on radiographs, such as the inferoposterior and posterolateral hip joint. CT arthrography, magnetic resonance imaging (MRI), and magnetic resonance arthrography with two-dimensional reconstructions can delineate labral abnormalities, cartilage lesions, and other intra-articular hip pathology. T2 and T2* mapping, delayed gadolinium-enhanced MRI of cartilage, T1rho, ultra-short echo time, and zero echo time are investigative MR techniques with promising evaluation of hip OA.
Keywords: hip; osteoarthritis; radiographs; computed tomography; magnetic resonance imaging; ultra-short echo time